Procedural Music in Games - Ayres, José Eduardo; Arthur, Pedro; Rolla, Vitor; Velho, Luiz (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2019: Anais do XVII Simpósio Brasileiro de Computação Musical, 2019)
This workshop will bring to the audience an introduction to the Chuck audio programming language, to the Unity game engine within a hands-on experience how one can use such technologies to achieve a new level of immersion through procedural generated sounds responding to game events and visual effects. The workshop is intended to a broad audience ranging from programmers to ones with little to no knowledge in the field.